2020
DOI: 10.1016/j.envres.2020.110177
|View full text |Cite
|
Sign up to set email alerts
|

Effects of long-term exposure to air pollutants on the spatial spread of COVID-19 in Catalonia, Spain

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
59
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(60 citation statements)
references
References 35 publications
1
59
0
Order By: Relevance
“…Similarly, an Italian study assessing air pollution exposure using PM 2.5 concentrations in Northern Italy municipalities found a positive association with mortality related to COVID-19, a 1 μg/m 3 increase being associated with a 9% increase in COVID-19 mortality (Coker et al, 2020). In addition, two Spanish studies found a higher incidence and mortality of COVID-19 in urban and industrial areas compared with rural areas in Tarragona (Marques et al, 2020), and an association between COVID-19 spread (including mortality) and nitrogen dioxide exposure in Catalonia (Saez et al, 2020). On the other hand, inconsistent results were reported from a study assessing the correlation between urban air pollution in the Milan metropolitan area and number of COVID-19 deaths, which found a negative correlation with air pollution assessed through surface levels of both PM 2.5 and PM 10 (Zoran et al, 2020b), and ground levels of nitrogen dioxide (Zoran et al, 2020a), but a positive one using ground levels of ozone, possibly due to the enhanced formation of outdoor airborne secondary aerosols (Zoran et al, 2020a).…”
Section: Discussionmentioning
confidence: 98%
“…Similarly, an Italian study assessing air pollution exposure using PM 2.5 concentrations in Northern Italy municipalities found a positive association with mortality related to COVID-19, a 1 μg/m 3 increase being associated with a 9% increase in COVID-19 mortality (Coker et al, 2020). In addition, two Spanish studies found a higher incidence and mortality of COVID-19 in urban and industrial areas compared with rural areas in Tarragona (Marques et al, 2020), and an association between COVID-19 spread (including mortality) and nitrogen dioxide exposure in Catalonia (Saez et al, 2020). On the other hand, inconsistent results were reported from a study assessing the correlation between urban air pollution in the Milan metropolitan area and number of COVID-19 deaths, which found a negative correlation with air pollution assessed through surface levels of both PM 2.5 and PM 10 (Zoran et al, 2020b), and ground levels of nitrogen dioxide (Zoran et al, 2020a), but a positive one using ground levels of ozone, possibly due to the enhanced formation of outdoor airborne secondary aerosols (Zoran et al, 2020a).…”
Section: Discussionmentioning
confidence: 98%
“…In our case, the Madrid region is an administrative unit that, in most cases, is quite heterogeneous. In any case, when, as in the region, this criterion is not met, the presence of measurement errors tends to underestimate the effect of the variable measured with error ( Saez et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Findings indicated that environmental pollutants, such as PM 10 , PM 2.5 , SO 2 , NO 2 and CO have a significant correlation with the COVID-19 epidemic in this US state. Saez et al (2020) explored the effect of long-term exposure to NO 2 and PM 10 as predictors of the spread of COVID-19 in Catalonia (Spain). Results suggested that, although some mechanisms may explain this relationship, the spatial spread of COVID-19 in Catalonia may be attributed to population interactions rather than immune sensitivity due to air pollution.…”
Section: Literature Reviewmentioning
confidence: 99%